PROFIL KEMAMPUAN BERPIKIR KREATIF BERDASARKAN TINGKAT BERPIKIR VAN HIELE SISWA KELAS VII DALAM MENYELESAIKAN SOAL SEGIEMPAT - Mukharomah, Umi Latifah; Hobri, Hobri; Setiawani, Susi (Kadikma, 2017)
Abstract. The ability of creative thinking is the ability to resulting new ideas or ways in a product. This is needed in solving math questions as well as geometric material. The study geometry will go through 5 levels according to van Hiele that is 0 (visualization), 1 (analysis), 2 (informal deduction), 3 (deduction), and 4 levels (rigor). This study aims to describe of students based on the thinking level of van Hiele in solving the geometry question. Based on the range scores is obtained by students, two students on the 0 level and two students on the 1 level including the 1 level of creative thinking that is less creative which is the the characteristics of students could show fluency in solving question. Two students in 1 level are also on the 1 level of creative thinking that is less creative but the range scores are differentiated. Two students in 2 levels are different on the level of creative thinking is creative and creative enough. Creative which is the characteristic of the student be able to show fluency, flexibility, and originality in solvinf question while creative enough with able to show fluency and flexibility in solving question. Keywords: creative thinking, level of van hiele thinking, quadrilateral